Extensive spin–orbit multi-reference study on low-lying electronic states of HgI. (January 2022) - Zhao, Shutao; Mo, Xinyi; Li, Rui; Guo, Huijie; Yan, Bing
Highlights: The accurate electronic structures of HgI are calculated with MRCI+Q method. The spin-orbit coupling effect is included in the calculation. Spectroscopic constants for bound states of HgI are obtained. Radiative lifetimes of B 2 Σ + 1/2, C 2 Π1/2 and D 2 Π3/2 of HgI are determined. The perturbations on the vibrational levels of the C 2 Π state are analyzed. Abstract: The multireference configuration interaction (MRCI) method with inclusion of Davidson correction (+ Q ) and spin-orbit coupling (SOC) effects is adopted to compute the electronic structures of the low-lying states of HgI. The potential energy curves (PECs) of 14 Λ-S states correlated with the first and second dissociation limits together with 30 low-lying Ω states are calculated. The spectroscopic constants of bound states are obtained, which agree well with the available experimental values. With the assistance of calculated SOC matrix elements, the perturbations on the vibrational levels of the C 2 Π caused by nearby state are analyzed. Finally, the spontaneous radiative lifetimes of bound states are evaluated, which are in consistence with existing measurements. Graphical abstract: Image, graphical abstract